What does it mean when we ask the public if they are ‘confident’ in policing? The trust, fairness, presence model of ‘public confidence’ - Morrell, Kevin (International journal of police science & management, 2020)
‘Confidence’ is widely taken to be a crucial measure of the relationship between citizens and public services such as policing. It is acknowledged that confidence is multifaceted and hard to measure, but often discussions are based on one ‘headline’ rating of a single item, for instance: ‘What is your level of confidence in…’. The subsequent focus for research is explaining what might drive ‘confidence’, or what it might predict. We are interested in a more fundamental question: what does it mean when we ask the public if they are ‘confident’ in policing? To answer this, we analyse extensive and detailed survey data specifically designed to measure public confidence, within the jurisdiction of a UK police force - West Midlands Police. We develop then validate a three-part model of confidence as trust, fairness and presence, and find good evidence to support this model across different waves of the survey. This extends existing literature with implications for policy.